Biologia e Ecologia da nidificação e variabilidade Genética de Centris (Centris) flavifrons Fabricius (Hymenoptera: Apidae, Centridini) - Peixoto, Marcella Pereira (2012)
Centris (Centris) flavifrons Fabricius, 1775 is a large solitary bee species and widely distributed in Neotropical region. The present study aimed to understand the nesting biology and the ecology of this species – in an urban area in João Pessoa city, Paraíba -, as well as its genetic variability. The specific study site of the nesting activities corresponds to a residential garden located in an urbanized area. The female behavior in the nests was observed in situ and through films, by using the method of marking these females. The establishment of the nests occurred on horizontal, sunny, sandy and bare surfaces, without grass. Over two years of study (comprising, therefore, two nesting periods) 286 nests were found forming an aggregate. The density of the nests in the whole area of the garden was 0.28 nests/m² monitored in the first period and 0.18 nests/m² in the second. The entrances of the nests had a circular shape, usually exposed, and typical amounts of sand located laterally to them. The average time spent by a female digging a nest was 3h and 40 min (n = 12). The average period of a nest activity was 6.9 days, ranging from two (n = 17) to 19 (n = 1) days. Cases of reactivation of nests, as well as invasion and possession of nests by other bees than its founder were observed. For the 434 observed flights, the average of daily flights for collecting floral resources was seven flights, with 82.7% of them occurred in the morning. Of this total, 75% of the flights were for pollen and 25% for oil collection. The time period of flights, both for pollen and for oil collection, increased throughout the day. It was verified an average of about five cells per nest, ranging from one up to a maximum of nine cells according to the duration of the nest. There was indirect evidence of Mesoplia sp. parasitizing nests of C. flavifrons. About its architecture, the excavated nests showed a main tunnel with branches at its end, due to the construction of more than one cell, which can be vertically aligned or not. In the "trap-pots" were found up to six cells from the same female. Overall, the dimensions of the cells did not varied much, showing capsular form, with rounded base and a cap arched at the apex, where there is a central process. Larvae were found in all larval instars, but pupae were not found. Genetic analyzes were performed using sequences of two mitochondrial genes regions as markers: cytb and COI. Most samples were collected during the study of nesting activities in João Pessoa (PB), while the others were collected in another location of Paraíba and Pernambuco. The haplotypes networks helped to observe that there are several mitochondrial haplotypes in samples from the main area of study in João Pessoa. Some haplotypes were found in more than one location. In this study, the data suggest that cytb gene was more informative than COI. However, some of the specimens did not show good performance in amplification reactions and, consequently, sequencing, or for a particular gene or both. Thus, to obtain more grounded results, genetic studies have to be continued.